Unraveling the Angiogenic Landscape in Endometrioid Endometrial Carcinoma: VEGF Expression, Histopathological Differentiation, and Lymphovascular Invasion as Key Players - Mustika Sari; Aswiyanti Asri; Tofrizal; Henny Mulyani; Syamel Muhammad; Husna Yetti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Endometrioid endometrial carcinoma (EEC) is a prevalent gynecological malignancy whose prognosis is influenced by factors including histopathological grade and lymphovascular invasion (LVI). Angiogenesis, crucial for tumor growth and metastasis, is significantly mediated by vascular endothelial growth factor (VEGF). This study aimed to investigate the expression of VEGF in EEC and its correlation with histopathological differentiation and LVI. Methods: This observational analytical study employed a cross-sectional design using 36 archival paraffin block samples of EEC diagnosed between January 2022 and December 2024 at the Anatomical Pathology Laboratory of Dr. M. Djamil General Hospital Padang. Cases were selected via simple random sampling from a population of 59. Histopathological grade (Grade 1, 2, or 3 based on FIGO architectural and nuclear criteria) and LVI (negative, focal, or substantial) were re-evaluated from Hematoxylin-Eosin (H&E) stained slides. VEGF expression was assessed by immunohistochemistry, scored semiquantitatively based on the percentage of positive tumor cells and staining intensity, and categorized as low or high. Data were analyzed using Chi-square tests, with p<0.05 considered statistically significant. Results: The mean age of patients was 54.36 years, with the highest prevalence in the 51-60 age group (41.7%). Grade 3 tumors were most common (38.9%), followed by Grade 2 (33.3%) and Grade 1 (27.8%). LVI was present in 47.2% of cases, predominantly focal (38.9%). High VEGF expression was observed in 58.3% of EEC cases. A statistically significant association was found between high VEGF expression and higher histopathological grade (p=0.000), with 66.7% of Grade 3 tumors showing high VEGF expression. No significant association was found between VEGF expression and LVI (p=0.080). Conclusion: High VEGF expression significantly correlated with higher histopathological grades in EEC, suggesting its role in tumor aggressiveness and dedifferentiation. However, a significant association with LVI was not established in this cohort. VEGF expression warrants further investigation as a potential prognostic biomarker and therapeutic target in EEC.